2019
DOI: 10.1590/0103-8478cr20180964
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of Lavandula dentata L. essential oils grown in Uberaba-MG

Abstract: The essential oils of the different parts of Lavandula dentata L. (inflorescences and aerial part without inflorescences) collected in the city of Uberaba (minas Gerais State)were obtained by hydro distillation, and their chemical composition was determined by gas chromatography coupled to mass spectrometry and compared to the chemical composition of essential oil of Lavandula hybrida and Lavandula officinalis. It was observed that the essential oils of the studied species have varied chemical composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
3
12
0
1
Order By: Relevance
“…[18] In most studies, the dominance of the oxygenated monoterpenes was confirmed, [10,16,17,22] but both the total number of compounds and the major compounds varied. According to this, different chemotypes were recognized in L. dentata, i. e., i) 1,8-cineole/β-pinene (like the one in this study) in samples from Algeria [23,24] and Mexico; [25] ii) linalool/linalyl acetate in specimens from Palestine [14] and one accession from Tunisia; [13] iii) 1,8cineole/camphor/fenchone in almost all published EO compositions for Brazilian specimens [12,26,27] and Tunisia. [11,15] Linalool and its acetic ester were commonly reported as main constituents in L. angustifolia Mill.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…[18] In most studies, the dominance of the oxygenated monoterpenes was confirmed, [10,16,17,22] but both the total number of compounds and the major compounds varied. According to this, different chemotypes were recognized in L. dentata, i. e., i) 1,8-cineole/β-pinene (like the one in this study) in samples from Algeria [23,24] and Mexico; [25] ii) linalool/linalyl acetate in specimens from Palestine [14] and one accession from Tunisia; [13] iii) 1,8cineole/camphor/fenchone in almost all published EO compositions for Brazilian specimens [12,26,27] and Tunisia. [11,15] Linalool and its acetic ester were commonly reported as main constituents in L. angustifolia Mill.…”
Section: Discussionsupporting
confidence: 50%
“…Our profile was one of the richest among those present in literature [11,29] and 1,8‐cineole (10) was confirmed as the main compound in samples coming from Morocco, [19] Tunisia, [11,15] Algeria, [30] and Brazil [3,12] . β‐Pinene (6) was well represented, in association with its isomer α‐pinene (2), in samples of different origin [22] .…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations